The Ca2+‐dependent interaction of calpastatin domain L with the C‐terminal tail of the Cav1.2 channel. Issue 5 (23rd January 2014) - Sun, Wei; Feng, Rui; Hu, Huiyuan; Guo, Feng; Gao, Qinghua; Shao, Dongxue; Yin, Dandan; Wang, Hongmei; Sun, Xuefei; Zhao, Meimi; Minobe, Etsuko; Sun, Yingxian; et al.
Abstract : To demonstrate the interaction of calpastatin (CS) domain L (CSL ) with Cav1.2 channel, we investigated the binding of CSL with various C‐terminus‐derived peptides at ≈ free, 100 nM, 10 μM, and 1 mM Ca 2+ by using the GST pull‐down assay method. Besides binding with the IQ motif, CSL was also found to bind with the PreIQ motif. With increasing [Ca 2+ ], the affinity of the CSL –IQ interaction gradually decreased, and the affinity of the CSL –PreIQ binding gradually increased. The results suggest that CSL may bind with both the IQ and PreIQ motifs of the Cav1.2 channel in different Ca 2+ ‐dependent manners. Abstract : Ca 2+ ‐dependence of calpastatin domain L (CSL ) binding with Cav1.2 was studied. Besides binding with the IQ motif, CSL was also found to bind with the PreIQ motif. With increasing [Ca 2+ ], the affinity of the CSL –IQ binding decreased. With increasing [Ca 2+ ], the affinity of the CSL –PreIQ binding increased. CSL may bind with two motifs of the Cav1.2 channel in a Ca 2+ ‐dependent manner.